2021
DOI: 10.12688/gatesopenres.13361.1
|View full text |Cite
|
Sign up to set email alerts
|

Testing for sensory threshold in drinking water with added calcium: a first step towards developing a calcium fortified water

Abstract: Background: Food fortification is an effective strategy that has been recommended for improving population calcium inadequate intakes. Increasing calcium concentration of water has been proposed as a possible strategy to improve calcium intake. The objective of this study was to determine the sensory threshold of different calcium salts added to drinking water using survival analysis. Methods: We performed the triangle test methodology for samples of water with added calcium using three different calcium salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Simulations in population groups of LMICs have shown that water with up to 500 mg of calcium per liter of water increases the percentage of people reaching adequate intake without exceeding the recommended upper limit for calcium intake 7 . In laboratory tests, we found that table water containing 20 mg of calcium per liter could reach up to 100 mg of calcium per liter by adding calcium chloride 31 . This water complied with WHO standards for tap water 31 .…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Simulations in population groups of LMICs have shown that water with up to 500 mg of calcium per liter of water increases the percentage of people reaching adequate intake without exceeding the recommended upper limit for calcium intake 7 . In laboratory tests, we found that table water containing 20 mg of calcium per liter could reach up to 100 mg of calcium per liter by adding calcium chloride 31 . This water complied with WHO standards for tap water 31 .…”
Section: Discussionmentioning
confidence: 56%
“…7 In laboratory tests, we found that table water containing 20 mg of calcium per liter could reach up to 100 mg of calcium per liter by adding calcium chloride. 31 This water complied with WHO standards for tap water. 31 Higher levels could be reached using organic salts; however, when using organic salts, the final water could only be distributed in containers or bottles or prepared at the point of use by adding the calcium salts.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations